Ganoderma lucidum Immune Modulator Protein rLZ-8 Could Prevent and Reverse Bone Loss in Glucocorticoids-Induced Osteoporosis Rat Model - Yong Yang; Tian Yu; Huan Tang; Zhihui Ren; Qianwen Li; Juan Jia; Hongyu Chen; Jun Fu; Shengchen Ding; Qiang Hao; Dan Xu; Liping Song; et al. (Frontiers Media S.A., 2020)
Immune modulation has been recognized as an effective anti-osteoporosis strategy since the pivotal role of the RANK/RANKL/OPG signaling in bone metabolism and remodeling was discovered. To investigate the potential preventive and/or therapeutic effects of immune modulator protein Ling Zhi-8 (LZ-8) on osteoporosis, the osteoporosis animal model was established in Wistar rats by intramuscular injection of dexamethasone (DEX), namely glucocorticoids-induced osteoporosis (GIOP) rat model. To investigate the potential preventive effect of rLZ-8 on GIOP, we co-treated the rats with DEX and rLZ-8 intraperitoneally during the GIOP modeling stage and analyze the bone mass measured by bone mineral content (BMC) and bone mineral density (BMD), as well as levels of phosphorus (Pi), calcium (Ca2+) and hydroxyproline (HOP) in femur of GIOP rats. Consistently, all results suggested that rLZ-8 could prevent bone loss in the femurs of GIOP rats. Through analyzing the trabeculae morphology and the trabeculae amount by H&E staining, we found rLZ-8 could also improve the structural deterioration in femurs of GIOP rats. In order to further verify the results and its mechanism obtained from bone analysis, multiple biomarkers, including minerals metabolism (Pi and Ca2+), bone formation markers (osteocalcin, ALP and IGF-1), bone resorption markers (TRACP5b, CTX-1 and HOP), cytokines (IL-1β, IL-6 and TNF-α), oxidative stress indicators (GSH-px, SOD and MDA) and hormone molecules (testosterone, estradiol, calcitonin and parathyroid hormone) have been detected in serum or urine of rats. Results of these biomarkers in serum or urine confirmed rLZ-8's protective effect in GIOP. Through analyzing the relative expression level of OPG and RANKL in femurs via western blot, we foundrLZ-8 could increase OPG/RANKL ratio which could impede osteoclastogenesis process. To test the potential therapeutic effect of rLZ-8 on successfully generated GIOP rats, we administrated rLZ-8 to rats for three weeks starting from the ending day of 7 weeks treatment of DEX. We found rLZ-8 could also reverse the bone loss in GIOP rats. Through the BWs and organ coefficient analysis, we found rLZ-8 has little toxicity to the rats. Our results suggested that rLZ-8 may be developed into promising anti-osteoporosis drug with both preventive and therapeutic properties.